2009
DOI: 10.1086/596742
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Production during Active Tuberculosis Is Regulated by Mechanisms That Involve IL-17, SLAM, and CREB

Abstract: Interferon-γ (IFN–γ) is crucial for protection against Mycobacterium tuberculosis, and the transcription factor cAMP response element binding protein (CREB) increases IFN-γ transcription. We determined whether the transmembrane receptor signaling lymphocyte activation molecule (SLAM) and interleukin-17 (IL-17) affect CREB phosphorylation and IFN-γ production in persons with tuberculosis. When T cells from patients with tuberculosis were activated with M. tuberculosis, 80% of SLAM+ T cells expressed phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 15 publications
4
38
1
Order By: Relevance
“…These findings are in line with our previous results demonstrating that Mtb -Ag stimulation of PBMC from TB produced lower IFN-γ levels but higher IL-17A amounts in comparison to HD2239. Moreover, we have also shown that high amounts of recombinant IL-17A in the cell culture inhibited the production of IFN-γ against the pathogen by PBMC23, according to our present data observed in AA TB, where we detected the lowest levels of IFN-γ in the presence of the highest levels of IL-17A (Fig. 4).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in line with our previous results demonstrating that Mtb -Ag stimulation of PBMC from TB produced lower IFN-γ levels but higher IL-17A amounts in comparison to HD2239. Moreover, we have also shown that high amounts of recombinant IL-17A in the cell culture inhibited the production of IFN-γ against the pathogen by PBMC23, according to our present data observed in AA TB, where we detected the lowest levels of IFN-γ in the presence of the highest levels of IL-17A (Fig. 4).…”
Section: Resultssupporting
confidence: 92%
“…To deeply investigate the hypothesis relating to the AA genotype of the rs2275913 SNP with protection against tuberculosis disease, we next analyzed plasma levels of IFN-γ and IL-17A, two crucial cytokines that participate in the immune response against Mtb 7222332. Then, we determined by ELISA the levels of these two cytokines among individuals carrying the different genotypes of the rs2275913 SNP (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of IL-17 downstream genes harbor NF-kB and C/EBP binding sites, both of them are necessary for IL-17-mediated promoter activity (Ruddy et al, 2004;Berger et al, 2006). For instance, CREB phosphorylation induced by IL17 could regulate IFN-g production in persons with tuberculosis (Pasquinelli et al, 2009). There were several putative transcription factor-binding sites located in 5 0 flanking region of CgIL17 genes, including the sites for C/EBP, AP-1, STAT, NF-kB, GATA and Oct-1, which were either directly or indirectly functionally related to immune responses in vertebrates (Cristina et al, 2009;Skjesol et al, 2010;Tripathi and Aggarwal, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Humans defective in genes for IFN-␥ or the IFN-␥ receptor are prone to serious mycobacterial infections, including M. tuberculosis. The regulation of IFN-␥ transcription is complex, involving multiple enhancer and repressor elements in response to mycobacterial Ags (12,17). Further work should continue to focus on the mechanism for decreased IFN-␥ production in TB patients, which will enrich our knowledge of protective immunity against M. tuberculosis and contribute to finding new strategies for the control and treatment of TB.…”
Section: Ifn-␥-producing T Cells Protect Against Acute Infection Bymentioning
confidence: 99%